2021
DOI: 10.35445/alishlah.v13i1.711
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Madrasah Principal in Teacher Performance Supervision

Abstract: This study aims to obtain in-depth information related to the role of school principals in supervising teacher performance. Supervised performance is related to teaching and learning activities. The principal carries out supervision to improve the quality of teacher performance. This study used a qualitative approach with a survey method. Data were collected using observation, interviews, and documentation. Data analysis consists of the data reduction process, data presentation, conclusion drawing, and triangu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The main focus of teaching supervision is to build the capacity of teachers to use new teaching and learning models. Collaboration can be established through dialogue between district leaders, schools, and teachers to see their views, concerns, and proposed solutions in the transition to an online learning model (Brock et al, 2021;Hakim, 2021). While Mette (2020) in his study found that teaching leaders play a role towards empowering teachers and students of different backgrounds and needs by providing equal opportunities for all students to gain knowledge and guidance.…”
Section: To Identify the Role That Instructional Leaders Need To Play...mentioning
confidence: 99%
See 2 more Smart Citations
“…The main focus of teaching supervision is to build the capacity of teachers to use new teaching and learning models. Collaboration can be established through dialogue between district leaders, schools, and teachers to see their views, concerns, and proposed solutions in the transition to an online learning model (Brock et al, 2021;Hakim, 2021). While Mette (2020) in his study found that teaching leaders play a role towards empowering teachers and students of different backgrounds and needs by providing equal opportunities for all students to gain knowledge and guidance.…”
Section: To Identify the Role That Instructional Leaders Need To Play...mentioning
confidence: 99%
“…They acted to establish an online community with teachers and parents (Brock et al, 2021). Instructional leaders meet with teachers individually to discuss their needs, strengths, and weaknesses and work together to identify professional learning planning and support to ensure successful online instructional delivery (Brock et al, 2021;Hakim, 2021). As a teaching leader, the principal makes personal contact with his staff through phone calls or text messages to ensure tasks are performed well and expresses appreciation for the dedication and commitment given to the school (Brock et al, 2021).…”
Section: To Identify the Role That Instructional Leaders Need To Play...mentioning
confidence: 99%
See 1 more Smart Citation
“…A more in-depth analysis of demand and supply is very important for planners because examining in more detail the two components can reveal various dynamic factors that affect demand and supply. Demand and supply are dynamic due to internal and external factors that dominantly influence them to continue to change and develop berkembang (Ginting et al, 2006), one of which is identified in the mastery of digital technology devices as a tool that can support educational implementation activities (Hakim, 2021).…”
Section: Analysis and Projection Of Needs And Provision Of Educatorsmentioning
confidence: 99%
“…The higher the use of digital technology in a madrasa, the higher the performance of the madrasah (Ibrahim et al, 2022). Research conducted by Hakim (2021) revealed that digital technology is a tool capable of supporting the activities/performance of implementing education. Aditama and Andari (2022) added that educational staff/educators must have practical learning skills or competencies in the Industrial Revolution 4.0 era.…”
Section: Introductionmentioning
confidence: 99%